Policy Strategy for Supporting Marriage Counseling in Reducing Divorce Trends - I Putu Putra Yasa; Trisula; Hamdan Tajori (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper outlines that the increasing divorce rate in Indonesia indicates the need for more effective policies to support family resilience. One factor contributing to this trend is the low level of awareness among couples about accessing marriage counseling. In developed countries, counseling is a normal part of married life, while in Indonesia, social stigma still hinders this. This paper analyzes this issue and the policies that can be implemented to normalize marriage counseling in Indonesia. The purpose of this policy paper is to formulate comprehensive policy recommendations to address the issues of marriage counseling support and communication, which are the root causes of divorce. A qualitative approach was chosen, emphasizing the U-Process analysis method. The results indicate that couples' awareness of accessing marriage counseling remains low. Individual mental models of each actor can be a barrier to accessing marriage counseling. The potential of religious and cultural leaders has not been fully utilized. Policy recommendations are directed to the Minister of Religious Affairs, religious and cultural leaders, and relevant institutions to support the normalization of marriage counseling through religious and cultural leaders. This approach is expected to create a paradigm shift in society that will be more open to marriage counseling. Marriage counseling becomes a necessity, not just a solution to conflict. This will strengthen family resilience, improve the quality of communication within the household, and reduce the divorce rate in Indonesia.